Die toekoms van die klein plattelandse gemeente - H. Jurgens Hendriks (HTS Teologiese Studies/Theological Studies, 2012)
The future of the small rural congregation. The article addressed the plight of small rural congregations by relating the results of three visits to ten congregations in the Western Cape and Karoo region of South Africa. The research goal was to help these congregations theologically become missional and kingdom focussed. As such it implied a transformation process, moving from a nationalistic-denominational and maintenance-institutional stance to that of getting the whole community’s involvement to address the burning local issues that affect all. The issues that surfaced and the process that was followed are described.